“DIFFICULT” FAMILY AS A FACTOR OF COMPLICATIONS IN GIRLS’ MENTAL DEVELOPMENT AND INDIVIDUAL PREVENTION - Yuldashevna , Karaketova Dilnoza (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article is devoted to the issue of the influence of a “difficult” family on the nature of the mental development of teenage girls. The need for an in-depth criminological study of the personality of minor girls is substantiated in order to develop practical proposals and recommendations used in the implementation of individual prevention